Problem drinking and exceeding guidelines for 'sensible' alcohol consumption in Scottish men: associations with life course socioeconomic disadvantage in a population-based cohort study - Benzeval Michaela; Emslie Carol; Lewars Heather; Batty G David; Hunt Kate (BMC, 2008)
Abstract Background With surveys suggesting that exceeding guidelines for 'sensible' alcohol intake is commonplace, the health and social impact of modifying intake on a population level is potentially considerable. If public health interventions are to be successfully implemented, it is first important to identify correlates of such behaviours, including socioeconomic disadvantage. This was the aim of the present study. Methods Population-representative cohort study of 576 men from the West of Scotland. Data on life course socioeconomic position were collected in 1988 (at around 55 years of age). Alcohol consumption patterns (detailed seven day recall) and problem drinking (CAGE questionnaire) were ascertained in 1990/2 (at around 59 years of age). A relative index of inequality was computed to explore the comparative strength of different indicators of social circumstances from different periods of the life course. Results Socioeconomic adversity in both early life and in adulthood was related to an increased risk of exceeding the weekly and daily alcohol guidelines, with adult indicators of socioeconomic position revealing the strongest associations. Of these, material indicators of socioeconomic deprivation in adulthood - car ownership, housing tenure - were marginally more strongly related to heavy alcohol intake and problem drinking than education, income and occupational social class. A substantial proportion of the influence of early life deprivation on alcohol intake was mediated via adult socioeconomic position. Similar results were apparent when problem drinking was the outcome of interest. Conclusion In men in this cohort, exposure to disadvantaged social circumstances across the lifecourse, but particularly in adulthood, is associated with detrimental patterns of alcohol consumption and problem drinking in late middle age.